An updated checklist of serpentinophytes for research andconservation in ultramafic ecosystems on the southernIberian Peninsula (Spain) - Pérez-Latorre, Andrés Vicente; Keen, Nazaret; Casimiro-Soriguer Solanas, Federico; Goncalves, Estefany; Hidalgo-Triana, Noelia (Wiley, 2024)
Although checklists are essential tools for managing and conserving ultramafic ecosystems, no updated checklist currently exists for ultramafic ecosystems on the southern Iberian Peninsula. Thus, the objectives of our study were (1) to create an updated checklist of serpentinophytes on southern Iberian Peninsula, (2) to determine whether the distribution of serpentinophytes is associated with certain specific types of ultramafic rocks, and (3) to calculate the abundance and richness of serpentinophytes per outcrop to guide conservation efforts. Following a methodology involving field work and searches of bibliographies and herbaria we produced an updated checklist containing 28 serpentinophytes (i.e., 23 obligates, one preferential taxon, one sub-serpentinophyte, and three regional serpentinophytes). The serpentinophytes showed different petrological affinity, where harzburgite–lherzolite and harzburgite–pyroxenite–dunite exhibited higher occupancy, possibly due to their mineralogical and chemical composition (e.g., containing heavy metals) and/or the larger surface area of those outcrops. We also observed that the occupancy of 21 species was higher in different petrographic entities, the reasons for which could be elucidated by future soil analyses. The highest richness of serpentinophytes was found in the main outcrop of Bermeja, followed by smaller outcrops of Alpujata, Aguas, and Guadalhorce Valley. Although the richness of Aguas resembled that of Alpujata, a notable difference emerged in some of its areas owing to bioclimatic and biogeographic isolation. Given the exclusive presence of serpentinophyte flora on the southern Iberian Peninsula, all southern Iberian outcrops should receive some form of conservation as protected natural spaces.
Keywords: Plantas serpentinícolas- Sierra Bermeja (Málaga); Conservation; Management; Petrographic entities; Serpentine flora; Sierra Bermeja